PENGARUH POTENSI DIRI, PERENCANAAN KARIR, TEMAN SEBAYA, BIAYA PENDIDIKAN, DAN STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA KELAS XII DI SMAS PP Dr.M.NATSIR - Kendra, Ropi; Yosi Eka Putri; Meri Rahmania (Journal of Practice Learning and Educational Development, 2026)
This study aims to determine (1) the influence of self-potential on the interest in continuing education to college in grade XII students at SMAS PP Dr.M.Natsir (2) the influence of career planning on the interest in continuing education to college in grade XII students at SMAS PP Dr.M.Natsir (3) the influence of peers on the interest in continuing education to college in grade XII students at SMAS PP Dr.M.Natsir (4) the influence of education costs on the interest in continuing education to college in grade XII students at SMAS PP Dr.M.Natsir (5) the influence of parental socioeconomic status on the interest in continuing education to college in grade XII students at SMAS PP Dr.M.Natsir. The time of this study was in August 2025. This type of research is associative research. The population in this study were grade XII students at SMAS PP Dr.M.Natsir. The sample numbered 33 people with a sampling technique in the form of total sampling. The research instrument used in this study was a closed questionnaire with multiple linear regression analysis testing. The data analysis technique used was descriptive and inductive analysis technique, with the help of Eviews 12 and SPSS version 25.0 programs. The results of the study showed that: (1) there is a significant influence between self-potential on the interest in continuing education to higher education with a coefficient value of -0.667, a calculated t value of 3.711 > t table of 1.692; (2) there is a significant influence between career planning on the interest in continuing education to higher education with a coefficient value of 0.505, a calculated t value of 3711 > t table of 1.692; (3) there is a significant influence between peers on the interest in continuing education to higher education with a coefficient value of 1.267, a calculated t value of 6.578 > t table of 1.692; (4) there is a significant influence between education costs on the interest in continuing education to higher education with a coefficient value of 0.330 and a calculated t value of 2.836>t table of 1.692; (5) there is a significant influence between the socio-economic status of parents on the interest in continuing education to higher education with a coefficient value of 0.430 and a calculated t value of 3.080>ttable of 1.692; (6) there is an influence of self-potential, career planning, peers, education costs, and the socio-economic status of parents together on the interest in continuing education to higher education with an Fcount of 39.145 > Ftable of 2.50. This is proven by the results of the study which states that F count 39.145 > F table 2.50 with a level of 0.000 < 0.05 based on the analysis of the coefficient of determination, the R square value is 0.879 which means 87.9%. while the remaining 13.1% is influenced by other variables not included in this study.